EVOLUTION OF THE ACADEMICIAN RIDGE ACCOMODATION ZONE IN THE CENTRAL PART OF THE BAIKAL RIFT, FROM HIGH-RESOLUTION REFLECTION SEISMIC PROFILING AND GEOLOGICAL FIELD INVESTIGATIONS - Mats V.D.; Khlystov O.M.; Batist M.De.; Ceramicola S.; Lomonosova T.K.; Klimansky A. (My University, 2000)
New high-resolution seismic reflection data from the central part of Lake Baikal provide new insight into the structure and stratigraphy of Academician Ridge, a large intra-rift accommodation zone separating the Central and North Baikal basins. Four seismic packages are distinguished above the basement: a thin top-of-basement unit; seismic-stratigraphic unit X; seismic-stratigraphic unit A; and seismic-stratigraphic unit B. Units A and B were cored on selected key locations. The four packages are correlated with a series of deposits exposed on the nearby western shores: the Ularyar Sequence (Oligocene); the Tagay Sequence (Lower to Middle Miocene); the Sasa Sequence (Upper Miocene to Lower Pliocene); the Kharantsy Sequence (Upper Pliocene); and the Nyurga Sequence (Lower Pleistocene). Based on stratal relationships, sedimentary geometries, distribution patterns and principal morphostructural elements – both onshore and offshore – we propose a new palaeogeographic evolution model for the area. In this model progressive tectonic subsidence of the Baikal basins and successive pulses of uplift of various segments of the rift margins lead to: (a) formation of the ridge as a structural and morphological feature separating the Central and North Baikal basins during the Middle to Late Miocene; (b) gradual flooding of the main parts of the ridge and establishment of a lacustrine connection between the two rift basins during the Late Miocene; and (c) total submergence of the top parts of the crest of the ridge during the latest Pleistocene. This new model helps to better constrain numerous phases in the structural evolution of the Baikal Rift, in which the Academician Ridge as an accommodation zone plays a crucial role.
Keywords: Miocene; Pliocene; Oligocene; Pleistocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Pliocene; Cenozoic::Neogene::Miocene